Resveratrol Delivery by Albumin Nanoparticles Improved Neurological Function and Neuronal Damage in Transient Middle Cerebral Artery Occlusion Rats - Xu, Huae; Hua, Ye; Zhong, Jie; Li, Xiaolin; Xu, Wei; Cai, Yingyuan; Mao, Yukang; Lu, Xiaowei (Frontiers in Pharmacology, 2018)
Human serum albumin (HSA) is an intrinsic protein and important carrier that transports endogenous as well as exogenous substances. We demonstrated the regional accumulation of albumin in the ischemia-reperfusion (I/R) brain, which providing the footstone for the application of HSA based nanoparticles in study of cerebral I/R injury. Resveratrol is potential in treatment of cerebral I/R injury but restricted for its water insolubility and short half-life in vivo. Herein, we prepared resveratrol (RES)-encapsulated by HSA nanoparticles (RES-HSA-NPs) to facilitate the application of resveratrol in protection from cerebral I/R injury. RES-HSA-NPs demonstrated spherical shape, a diameter about 100 nm, a highest resveratrol encapsulation efficiency of 60.9 ± 5.07%, and controlled release pattern with the maximum release ratio of 50.2 ± 4.91% (in pH=5.0 PBS) and 26. 2 ± 2.73% (in pH=7.4 PBS), respectively, after 90h incubation at 37 °C. After intravenous injection into transient middle cerebral artery occlusion (tMCAO) rats, RES-HSA-NPs improved neurological score and decreased infarct volume at 24 hours after tMCAO in a dose dependent manner. A single dose of 20 mg/Kg RES-HSA-NPs via tail vein improved neurological outcomes and decreased infarct volume at 24 h and 72 h in tMCAO rats. Ischemia-reperfusion increased oxidative stress (indicated by products of lipid peroxidation, MDA) and neuronal apoptosis (indicated by yellow-brown TUNEL-positive cells), 20 mg/Kg of RES-HSA-NPs via tail vein administration significantly attenuated oxidative stress and neuronal apoptosis. These results demonstrated the potential of RES-HSA-NPs in therapy of cerebral ischemia-reperfusion injury.